Histological Value of Duodenal Biopsies - Limci Gupta; Hamid B. (The Scientific World Journal)
This study was performed to see the value of histopathological diagnosis in management of patients with duodenal biopsies; to look for correlation of histology and serology in suspected cases of coeliac disease; the reasons for taking duodenal biopsies and whether proper adequate histories are provided on the forms sent with request for histopathological view on duodenal biopsies. Here are the observations of the study followed by the discussion.